Higher Education and Research: The Utmost Priority of a Nation Dr. Priti Verma Head of the Department, English, - Verma, Dr. Priti (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Today, we are living in the world which encompasses abundant knowledge. The contemporary world is the world of internet and communication with ever-increasing bulk of vast knowledge. Knowledge, which we generally acquire through our surroundings, experiences and of course, education. Education is one of the most crucial requirements. It is not machines, land, property or capital, but human brain which is the most important asset to any family, community and nation. Thus we have to safeguard the system of education and improve it further for socio-economic development. Keywords: Higher Education, internet and communication.